The effect of building information modelling implementation on sustainable project performance in the construction industry: a mediating impact of circular economy practices - Mohammed Akmal Hanif, Ismail (2023)
This research is present about the effect of building information modelling implementation on sustainable project performance in construction industry: a mediating impact of circular economy practices in Malaysia by using a Natural-Resource-Based View (NRBV) framework. The objectives of this study is to investigate the relationship between BIM implementation and circular economy practices, to investigate the relationship between BIM implementation and sustainable project performance, to investigate the relationship between circular economy practices and sustainable project performance and to investigate the mediating effect of circular economy practices on relationship between BIM implementation and sustainable project performance. This study was conducted using stratified method sampling and send the questionnaire via the company’s emails. From these findings, the BIM implementation in Malaysian construction company are currently in developing progress as construction companies to have sustainable project performance. The implication of this study is the theoretical implication would be benefits to the other research to reach the gaps on adding more extensive studies on circular economy in Malaysian construction industry while the practitioner’s industry can apply circular economy effectively in reducing the material consumption in construction industry in Malaysia.